2010
DOI: 10.3354/ame01404
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of dissolved organic matter and microbial activity in the coastal North Sea

Abstract: The dynamics of dissolved organic matter (DOM) and microbial activity were monitored in the coastal North Sea over an annual cycle. DOM accumulated during the spring bloom towards the summer, associated with high phytoplankton extracellular release. Accumulation of dissolved organic carbon (DOC) occurred from April to June. During this period, based on the bacterial carbon demand (BCD) of the free-living bacteria and the photosynthetic extracellular release (PER), 85 µM C were derived from sources other than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
4
25
1
Order By: Relevance
“…This means that the initial qualities of DOC and DON (as specified in Table 2), determined by the catchment characteristics, were the major factor defining the biodegradability of DOC and DON, which supports our main hypothesis. Bioavailability of DOM has been previously reported to have strong seasonal variation (Lønborg et al, 2009;Sintes et al, 2010). However, in the experiments presented here the season surprisingly did not have significant effect on DOC and DON degradation in spite of the seasonal changes in DOM quantity and quality in study estuaries (Fig.…”
Section: Doc and Don Degradationcontrasting
confidence: 37%
“…This means that the initial qualities of DOC and DON (as specified in Table 2), determined by the catchment characteristics, were the major factor defining the biodegradability of DOC and DON, which supports our main hypothesis. Bioavailability of DOM has been previously reported to have strong seasonal variation (Lønborg et al, 2009;Sintes et al, 2010). However, in the experiments presented here the season surprisingly did not have significant effect on DOC and DON degradation in spite of the seasonal changes in DOM quantity and quality in study estuaries (Fig.…”
Section: Doc and Don Degradationcontrasting
confidence: 37%
“…In coastal upwelling systems, similar trends have been observed in which a high percentage of accumulated OM is partitioned into the particulate phase during exponential bloom conditions (Doval et al 1997, Wetz & Wheeler 2003, with evidence of greater DOM partitioning during later phase of the bloom (Hill & Wheeler 2002). Sintes et al (2010) assessed the seasonal variability of DOM and bacterioplankton dynamics in the coastal North Sea and observed a seasonal transition in the source of organic carbon that supported bacterial carbon demand (BCD). They demonstrated a pronounced seasonal pattern in DOM and found that extracellular release (ER) from primary production (PP) could account for BCD in spring and summer but that in winter periods the accumulated DOM was also required to partially support BCD.…”
Section: Introductionmentioning
confidence: 61%
“…7). This paradox seems to be widespread and has been found in other regions of the Mediterranean (Zweifel et al 1995, Cauwet et al 1997, Thingstad et al 1997, Avril 2002 and in distinct places worldwide (Carlson et al 1994, Guo et al 1995, Hansell & Carlson 1998b, Sintes et al 2010. The magnitude of the increase in DOC concentration through the seasons is not always the same.…”
Section: Discussionmentioning
confidence: 96%
“…DOC is produced through different processes, such as phytoplankton excretion, egestion and release by grazers, viral cell lysis, and the enzymatic hydrolysis of detritus and aggregates (Biddanda & Benner 1997, Biersmith & Benner 1998, Fajon et al 1999, Nagata 2000, Sintes et al 2010, and heterotrophic bacteria are the main consumers of DOC. Decoupling between production and consumption processes can cause the accumulation of DOC.…”
Section: Introductionmentioning
confidence: 99%